Activity and mRNA expression levels of selected cytochromes P450 in various sections of the human small intestine. Issue 6 (13th April 2019) - Clermont, Valérie; Grangeon, Alexia; Barama, Azemi; Turgeon, Jacques; Lallier, Michel; Malaise, Jacques; Michaud, Veronique
Abstract : Aims: To characterize mRNA expression levels (17 cytochromes P450) and activity (9 isoforms) of major cytochromes P450 expressed throughout the human small intestine. Methods: Tissue samples were obtained from 9 deceased subjects and intestinal sections ( n  = 10) were isolated for each subject. Relative mRNA expression levels were determined using quantitative real‐time PCR. Intestinal microsomes were prepared from 5 subsections: duodenum, jejunum (proximal and mid‐jejunum) and ileum (proximal and mid‐ileum) regions. In vitro incubations were performed with various cytochrome P450 probe substrates: bupropion (CYP2B6), repaglinide (CYP2C8), tolbutamide (CYP2C9), S‐mephenytoin (CYP2C19), bufuralol (CYP2D6), chlorzoxazone (CYP2E1), ebastine (CYP2J2), midazolam (CYP3A4/5) and lauric acid (CYP4A11). Metabolite formation was assessed using validated liquid chromatography–tandem mass spectrometry assays. Results: Cytochrome P450 mRNA levels ranked as follows: CYP3A4 > CYP2C9 > CYP2C19 > CYP2J2 > CYP4F2. Cytochrome P450 mRNA transcripts showed different patterns in their relative expression from 1 region to the other but CYP3A4, CYP2C9, CYP2C19 and CYP2J2 displayed the highest levels of mRNA expression (>5%) in all intestinal sections. Cytochrome P450 activities were greater in proximal part of the small intestine with the jejunum showing the greatest drug‐metabolism activity. Spearman's correlation analyses indicated that cytochrome P450 mRNA expressions and corresponding cytochrome P450 activities in the human intestine were moderately associated for CYP2C19, CYP2D6 and CYP4A11 (rs  = 0.44–0.56). Conclusions: Our study provides new and additional information on the expression and activities of selected cytochromes P450 in various sections of the human small intestine.